Narrative Inquiry in the Interpretative Approach ? Methodological Clue - Bartosz, Bogna; Żurko, Magdalena (INSTED: Interdisciplinary Studies in Education & Society, 2014)
The purpose of the article is to present a specific nature of an interpretative approach in psychological qualitative research. To be more precise, it is aimed at conducting research, analysis and interpretation of narrative materials in a way that is coherent with a theoretical model. The proposed research procedure is a result of the authors? long term experiences in using a narrative method in an interpretative model of psychological qualitative research based on M. Straś-Romanowska?s concept (1992). The research procedure is presented on an example of examining ways of experiencing a divorce by women with various length of post-divorce life and different autobiographical experiences.